The Death Penalty for Foreign Drug Offenders in China: Legal Protection and Equal Treatment - Liu, Siyu (European journal on criminal policy and research, 2019)
China has been under international pressure for the death sentences meted out to foreigners for drug-related offenses. Domestically, the sentencing of foreign offenders is perceived to be too lenient compared to that of the natives under similar circumstances. We discuss the due process protections in processing foreigners charged and convicted for capital drug offenses within the context of international law. Further, to empirically assess the sentencing of such cases, we use a sample of 192 cases including both offender groups to examine the role of citizenship status, case characteristics, and defense arguments on the outcome of either an immediate or suspended death sentence. Findings indicate that foreign offenders raise different defense arguments compared to that of native offenders; but citizenship status does not play a key role in the multivariate model; rather the number of defense arguments accepted by the court and the processing time help predict the sentencing outcome.